The effects of LED light spectrum manipulation on growth and color performance of giant gourami Osphronemus gouramy Lacepede Padang strain - Bambang Kusmayadi Gunawan; Kukuh Nirmala; Dinar Tri Soelistyowati; Daniel Djokosetiyanto; Wildan Nurussalam (Jurnal Akuakultur Indonesia)
This study aimed to evaluate the effect of light spectrum on growth and color performance of giant giant gourami Padang strain. The experiment used a completely randomized design (RAL) with four light emitting diode (LED) treatments in  different emission spectra (white, red, green, and blue) at 550 Lux intensity, compared to the control treatment (light room with white tubular lamp at 50 Lux intensity). The irradiation was carried out for 12 hours of photoperiod. The fish used had the total length of 82.90±4.2 mm and body weight of 9.87 ± 0.99 g. The highest growth performance was found in blue LED treatment with the specific growth rate of  2.73 ± 0.2% and feed efficiency of 86.26 ± 2.71%. The best color performance was found in red LED treatment with the RGB ratio of 44.57 ± 0.62% in dorsal fin, 38.41 ± 1.36% in pectoral fins, and 45.33 ± 2.25% in anal fin with the chromatophore cell concentration at 1.973±58 cells/mm2.